Influence of paternal education on maternal and child health outcomes in Sub-Saharan Africa: evidence from demographic and health surveys - Joshua Okyere; Demisu Zenbaba Hey; Sanni Yaya (Reproductive Health)
Abstract Background Maternal and child health outcomes remain pressing challenges in Sub-Saharan Africa (SSA), characterized by persistently high under-five mortality and inadequate utilization of essential maternal healthcare services. While the impact of maternal education on these outcomes is well documented, the influence of paternal education remains underexplored. This study investigates the association between paternal education and maternal health service utilization, focusing on antenatal care (ANC) and skilled birth attendance (SBA), as well as child survival across 22 SSA countries. Methods We conducted a cross-sectional analysis using nationally representative data from Demographic and Health Surveys (DHS) administered between 2013 and 2024 in 22 SSA countries. The study sample included a weighted total of 109,818 children aged 0–59 months and their mothers. Key outcomes included maternal healthcare utilization (≥ 4 ANC visits and SBA) and child survival. Paternal education was classified into three categories: no education, primary education, and secondary or higher education. Logistic and ordered logistic regression models were employed, adjusting for maternal, child, household, and regional covariates. Results Overall, 96.5% (95% CI: 96.4–96.6%) of children survived to age five, while 61.8% of mothers reported ≥ 4 ANC visits and 73.8% had skilled birth attendance. Higher paternal education was significantly associated with increased maternal healthcare utilization. Women whose partners had secondary or higher education were nearly twice as likely to attend ≥ 4 ANC visits (AOR: 1.99; 95% CI: 1.91–2.07) and more likely to access SBA (AOR: 1.60; 95% CI: 1.52–1.67) than those whose partners had no education. Marked regional and socioeconomic disparities persisted, with Southern SSA showing more favorable outcomes than Central and Eastern regions. Conclusion Paternal education is strongly associated with improved maternal healthcare utilization, which is itself linked to enhanced child survival in SSA. Although no direct relationship was found between paternal education and child survival, these findings underscore the indirect but influential role fathers play in shaping health outcomes. Targeted strategies that promote male educational attainment and actively involve fathers in maternal and child health interventions—particularly in underserved regions—are essential for reducing health disparities and improving outcomes across the region.